PENGARUH AKTIVITAS ORGANISASI TERHADAP PRESTASI BELAJAR (Studi Kasus Pengurus BEM Universitas Riau Kabinet Inspirasi Periode 2016-2017) - Mahmudi Pradayu; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at the University of Riau precisely in the secretariat of BEM University of Riau. Differences in views between students who follow organizations and students who do not follow the organization that causes authors interested in researching this issue. With the formulation of how the influence of organizational activity on the achievements of the Board of BEM University of Riau and what are its factors. The purpose of the study to determine the effect of organizational activity on learning achievement. The theory used is organization theory, interaction theory, motivation theory, achievement theory by using descriptive Quantitative research method. How to get data by observation and questionnaire. The results of this study can be known the influence of organizational activity on learning achievement and the factors that influence it. In this study note that organizational activity has a positive influence on the board that follows it. One of the positive effects yag gained is able to manage the time between organizations with college, good communication. The influence is influenced by several factors, both internal and external. Internal factors come from self like parents, front masses, competition and confidence. While external factors such as friends, thinking patterns and views, the soul of competition and organizational experience.Keywords: Organizational Activity, Learning Achievement